The direct costs of multiple sclerosis-study in the Czech Republic - Maresova, Petra; Valis, Martin; Novotny, Michal; Pavelek, Zbyšek; Kuca, Kamil (Neurological sciences, 2018)
BACKGROUND: Multiple sclerosis (MS) is a progressive autoimmune disease of the central nervous system that is often disabling and for which there is currently no cure, though disease-modifying treatment is now available. The aim of this study is to describe the current values of the direct costs of multiple sclerosis (MS) in the Czech Republic. METHODS: Attention is focused on direct medical costs. The costs were monitored in the Czech Republic among 5673 patients in the period between 2011 and 2015. These costs included complex, special and targeted visits at the neurologist, blood collection and the costs of hospitalisation. The results refer to the diagnoses according to the International Statistical Classification of Diseases and Related Health Problems. The attention is focused on MS G35 (NS; brain stem; spinal cord; disseminated; generalised). RESULTS: The average total direct costs per patient per year are 4838.1 €. Not every patient has to be hospitalised during the year, and not every patient has prescribed medication. According to the above data, 12% of patients are hospitalised and 55% of patients are prescribed medication. The minimum average cost per patient without medication and hospitalisation is 54.1 €. CONCLUSION: Cost evaluation across countries is difficult due to the different evidence. If only selected direct costs considered in this study are compared, the absolute economics burden increases over time. The only statistically significant difference in the average price and the time spent is between 2012 and 2013, where the correlation value is 0.597.
Keywords: Neurological disease; Female; ženské pohlaví; lidé; Cost of Illness; Multiple Sclerosis; roztroušená skleróza; hospitalizace; retrospektivní studie; Male; náklady a analýza nákladů; Czech Republic; Hospitalization; Česká republika; mužské pohlaví; Multiple sclerosis; Retrospective Studies; osobní újma zaviněná nemocí; Direct costs; Costs and Cost Analysis; Humans